Ethnographic Study at a Music Library Found Students Prefer Short Stopovers and Longer Solitary Study - Dominique Daniel (Evidence Based Library and Information Practice, 2014)
Objective – To identify patterns of patron behaviour in the library in order to improve space utilization.